Pengaruh Penambahan Tepung Daun Kelor (Moringa Olaifera) dalam Ransum terhadap Kualitas Karkas dan Non Karkas Ayam KUB: Pengaruh Penambahan Tepung Daun Kelor Dalam Ransum Terhadap Kualitas Karkas dan Non Karkas Ayam KUB - Pratama, Iswanto; Nealma, Samuyus; Reza Jatnika, Ahmad (Fakultas Ilmu dan Teknologi Hayati Universitas Teknologi Sumbawa, 2025)
The Balitbangtan KUB chicken is a new superior variety of native chicken produced by the Agricultural Research and Development Agency. To increase the productivity of KUB chickens, high-quality feed is required. One local feed that has good nutritional value for chickens is the Moringa (Moringa oleifera) plant. Moringa, a type of legume, can be used as a source of protein for chicken growth. This study aimed to determine the effect of Moringa leaf meal on the growth quality of KUB chickens. Twenty 8-week-old KUB chickens were allocated to this study and divided into four treatment groups: (p0) = treatment without Moringa, (p1) = treatment with 2% Moringa leaves, (p2) = treatment with 5% Moringa leaves, and (p3) = treatment with 10% Moringa leaves. Data were analyzed statistically using the independent sample t-4 test or unpaired t-test using Microsoft Excel. Observed parameters included daily body weight gain, body weight gain, carcass weight, and non-carcass weight. The results showed that the addition of KUB chicken feed significantly affected the average final body weight of 1,300 g/chicken over 18 weeks, with a body weight gain of 600 g/chicken, a slaughter weight of 1,300 g, a carcass weight of 5,720 g/chicken, and a feed conversion ratio of 5.15. Meanwhile, the average final body weight of 1,207 g/chicken over 4 weeks was 1,300 g.